A research protocol using ECG monitoring for detection of palpitations-associated arrhythmias in breast cancer survivors - Ying Sheng; Matthew R. Fleming; Jessica Mezzanotte-Sharpe; Nethmi S. Hewavithana; Sadie B. Sommer; Mary S. Dietrich; Janet S. Carpenter (PLoS ONE, 2025)
Palpitations are common but understudied in breast cancer survivors (BCS). Palpitations may relate to severe arrhythmias, resulting in life-threatening events or cardiac death. However, how palpitations relate to arrhythmias and electrocardiogram abnormalities is unknown. The purpose of the proposed project is to demonstrate the feasibility of using wearable electrocardiogram (ECG) monitors in BCS to detect and characterize arrhythmias associated with self-reported palpitations and to gain a comprehensive understanding of palpitations using an investigator-designed Palpitations Assessment Tool (PAT). We will conduct a prospective cohort study of 84 BCS (54 BCS with palpitations and 30 without). Eligible participants will include breast cancer patients who completed chemotherapy at least six months ago and no more than three years ago. Palpitations and arrhythmias will be recorded using an ECG monitor for two 7-day periods, one month apart. Feasibility, acceptability, and retention, as measured by completion of the PAT and monitored wearing for 7 days, will be evaluated using frequency distribution in recruitment and retention logs. We will generate descriptive summaries of the prevalence of primary outcomes, including frequency of palpitations and changes in cardiac rate and rhythm, and examine associations between these outcomes.